The effect on the job satisfaction organization, performance of employees commitment, and service performance - Tetra Hidayati; Rahmawati Rahmawati (Faculty of Economics and Business Mulawarman University, 2016)
The purpose of this study analyzes the effect of job satisfaction on organizational commitment and performance of employees as well as the performance of health centerservices in Kalimantan Timur. This research uses Structural Equation Model (SEM) with PLS Software for data processing. Data were collected from employees on the front line health center in Kalimantan Timur. The unit of analysis used in this research are health centers in Kalimantan Timur region is represented by three cities each district namely; Samarinda, Kutai, and Balikpapan each city district 10 health centers so that the total sample was 30 health centers. The result of the study found that job satisfaction had significant positive effect on organizational commitment; job satisfaction did not havesignificanteffecttoinfluence on employee performance; job satisfaction did nothave significantly affect the performance of the services; organizational commitmentdid nothave significant effect on employee performance; organizational commitment did not have significant effect on the servicesperformance; andthe performance of employees did not have significant effect on the servicesperformanceKeywords: job satisfaction, organizational commitment and performance of employees and service performance